Remarques sur le nouveau droit de la famille et le droit des successions - Castelli, Mireille (Les Cahiers de droit, 1984)
Recent changes in Family Law have indirectly brought on changes in the law of successions. On two points, however, proposed solutions are uncertain. The first point involves adoption and the relative scope of Articles 626 and 623 of the Québec Civil Code. Do the effects of the adoption go back in time to the day that the placement application for adoption was filed in the event that one of the adopters is deceased some time between the petition for placement and the application for adoption ? The second point concerns the effects of natural filiation. Does Article 594 of the Québec Civil Code eliminate all differences between the two kinds of filiation ?